2003
DOI: 10.1093/jn/133.7.2485s
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Histone Deacetylase Activity by Butyrate

Abstract: This article reviews the effects of the short-chain fatty acid butyrate on histone deacetylase (HDAC) activity. Sodium butyrate has multiple effects on cultured mammalian cells that include inhibition of proliferation, induction of differentiation and induction or repression of gene expression. The observation that butyrate treatment of cells results in histone hyperacetylation initiated a flurry of activity that led to the discovery that butyrate inhibits HDAC activity. Butyrate has been an essential agent fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
894
4
19

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,150 publications
(941 citation statements)
references
References 82 publications
24
894
4
19
Order By: Relevance
“…As HDAC3 silencing did not increase p21 WAF1/Cip1 expression in IGROV-1 cells (Figure 1b), it is also possible that the mechanism by which HDAC4 represses the p21 WAF1/Cip1 promoter varies between cell types. We found that Sp1 physically associates with HDAC4 and HDAC1, but does not interact with HDAC3 as reported (Doetzlhofer et al, 1999;Sun et al, 2002;Davie, 2003;He et al, 2005;Kang et al, 2005). We therefore speculate that HDAC4 participates, with a HDAC1-dependent co-repressor complex, in p21 WAF1/Cip1 repression.…”
Section: Discussionsupporting
confidence: 77%
“…As HDAC3 silencing did not increase p21 WAF1/Cip1 expression in IGROV-1 cells (Figure 1b), it is also possible that the mechanism by which HDAC4 represses the p21 WAF1/Cip1 promoter varies between cell types. We found that Sp1 physically associates with HDAC4 and HDAC1, but does not interact with HDAC3 as reported (Doetzlhofer et al, 1999;Sun et al, 2002;Davie, 2003;He et al, 2005;Kang et al, 2005). We therefore speculate that HDAC4 participates, with a HDAC1-dependent co-repressor complex, in p21 WAF1/Cip1 repression.…”
Section: Discussionsupporting
confidence: 77%
“…Effects of SB on the expression level of acetylated histone H2B As butyrate is known to induce histone acetylation [4,8], the degree of this acetylation was examined. Western blot analysis using an anti-acetylated histone H2B antibody showed that SB at a concentration of 2 mM significantly induced the accumulation of acetylated histone H2B under 6, 12 and 24 h of SB treatment, with levels that were approximately 3.5 times higher than those of control cells (0 h) ( Fig.…”
Section: Effects Of Sb On Cell Growth and Ap Activitymentioning
confidence: 99%
“…3). It has been shown that butyrate inhibits HDAC classes I, IIa and IV (Davie 2003). This compound leads to growth arrest, differentiation of leukemic cells and induces apoptosis following the deterioration of the anti-apoptotic protein Bcl-2 (Rosato et al 2003;Schnekenburger et al 2006).…”
Section: Hdac Inhibitors Of Natural and Dietary Originsmentioning
confidence: 99%